Towards 'purifying' the understanding of Allah - Abd Razak, Dzulkifli (2008)
In the name of Allah, Most Gracious, Most Merciful. Say: He is Allah, the One and Only! Allah, the Eternal, Absolute; He begetteth not nor is He begotten. And there is none like unto Him. THE above is a translation by Abdullah Yusuf Ali, of an important surah (or chapter) 112 named AlIkhlas (Purification of the Unity of Allah), of the Quran. It is recorded as one of the earliest revelations by Allah to the Prophet Muhammad aimed at "purifying" the understanding of Allah. The word ikhlas is derived from the Arabic root which means to be purified or refined, reemphasising the significance of the Oneness (Unity) of Allah as the central message in Islam. After all, the Oneness of Allah or Tauhid is the very foundation of everything Islam.